Phytochemical screening, antimicrobial and antioxidant efficacy of some plant extracts and their mixtures - Mahmood, Mahmood H.; Osama, A K; Makky, Essam A. (IOP Publishing, 2019)
Abstract. Various phytochemicals and bioactive compounds are sourced from medicinal plants.This study focused on finding the most potent plant extracts whose combination could exhibit betterantioxidant and antimicrobial activities compared to the efficacy of the individual extracts. The combined plant extracts were O. stamineus, E. longifolia, A. bilimbi, P. granatum, and M. nigra.Ultrasound extraction technique was used for the extraction of the plant material before screeningthe extracts for the presence of several phytochemical groups. After the screening for the presenceof phytochemicals, the extracts were evaluated for antimicrobial activity against fivemicroorganisms (S. aureus, B. subtilis, P. vulgaris, E. coli, and C. albicans) at 3 differentconcentrations (600, 400 and 200 mg/mL) using disc diffusion method. The aim of this antimicrobialscreening was to identify and select the most potent extracts for the combination study. From thescreening result, P. ganatum and M. nigra had the highest antimicrobial activity against all the testedorganisms, as well as the highest DPPH radical scavenging activity of 95.40 % (IC50 = 120.2 μg/mL)and 90.20 % (IC50 = 330.0 μg/mL), respectively. Hence, both extracts were combined and screenedf or antimicrobial and antioxidant activities at the same concentration range but at differentcombination ratios of 1:1, 1:2 and 2:1 (v/v). The results showed the extract mixtures at differentcombination ratios of 1:1, 1:2 and 2:1 (v/v) to exhibit good antioxidant and antimicrobial activities. However, the combination ratio of 1:1 gave the best antioxidant activity as it achieved an IC50 value of 82.0 μg/mL. Therefore, it is concluded that the mixture of the selected extracts exhibited strongantioxidant and antimicrobial activities, coupled with a significant level of antifungal activity.